(untitled) (Nigerian Journal of Physiological Sciences, 2022)
In spite of the overwhelming patronage of the plant Jatropha tanjorensis (J.T) popularly called “Hospital Too Far” by pregnant and women of reproductive age for its supposed reproductive benefits, the scientific evidence are hardly known. This study thus sought to examine the effect of consumption of aqueous leaf of J.T extract on female fertility potential and gestational outcome using forty (40) virgin female Wistar rats weighing 120-150g. The extract LD50 was >5000 mg/kg. The female rats were divided into unmated and mated groups (n=10 rats per subgroups). Group A (unmated group) consisted of control which received 0.2mL of normal saline (vehicle) and J.T-treated which received 500mg/kg (orally) once daily for 28 days. For Group B (mated group), the treated dams received 500 mg/kg (orally) once daily prior to mating (2 weeks), during mating (1 week) and throughout gestation, while the control received 0.5ml of physiological saline orally during the same period. All animals had free access to food and water. For the unmated group, after 28 days of treatment samples were collected for hormonal assay. J.T increased follicle stimulating hormone (FSH) and estrogen. For subgroup B, the extract was assessed for it reproductive and gestational performance, as well as pregnancy outcome. Nine (9) J.T-treated rats against seven (7) of control got pregnant. J.T increased mean weight gain, food and water intake. The Birth weight, body length and tail length of pups whose mothers were treated with the aqueous leaf extract of J.T increased significantly. Intake of J.T was effective in boosting female reproductive health, pregnancy health and outcome